Kocenov srednješolski atlas kot didaktična prelomnica - Birsak, Lukas (Geografija Slovenije, 2011)
This monograph ('Kozenn's school atlas as a milestone in education') was released on the 150th anniversary of the publication of the first secondary-school atlas by Blasius Kozenn (a.k.a. Blaž Kocen). He grew up in a Slovenian farming family near Ponikva, Lower Styria. While working as a teacher, he realized he needed more new teaching aids and he advocated more modern methods of teaching. His cooperation with the publisher Eduard Hölzel was of key importance. Kozenn's crowning accomplishment was the first successful school atlas in the Austrian Empire, published in 1861. It contained twenty-seven maps, of which three were on double pages, and was published in German, Hungarian, Czech, and Polish. The author followed the example of the leading German atlases of that time, but he thoroughly adapted it to local conditions, introduced several important new features, and ensured that its reprints and other atlases that used his as a model were constantly technically, artistically, and conceptually improved. Kozenn's secondary-school atlas soon became the leading one in the German-speaking part of the empire, whereas in the Czech, Polish, and Hungarian schools his "small" atlases, which were more limited in their coverage and cheaper, were initially more successful. After Kozenn's death, the publisher decided to maintain his well-established brand, and so even 150 years since its first publication the Kozenn-Atlas is still a prominent name.